2014
DOI: 10.1144/sp412.5
|View full text |Cite
|
Sign up to set email alerts
|

Muscovite 40 Ar/ 39 Ar ages help reveal the Neogene tectonic evolution of the southern Annapurna Range, central Nepal

Abstract: We present new muscovite 40 Ar/ 39 Ar ages from thirteen Greater Himalayan rocks and one Lesser Himalayan rock collected from four north-trending transects across the southern Annapurna Range. Combining the new data with previously published ages leads to the following new insight into the tectonic development of the southern Annapurna. Muscovite cooling ages from Greater Himalayan rocks are c. 16-10 Ma in the western Annapurna and c. 6-2 Ma in the eastern Annapurna, revealing a decrease of 4 -14 Ma from west … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 86 publications
3
43
0
Order By: Relevance
“…Timing of MCT cooling varies non‐systematically along strike, with the latest and most rapid cooling at Marsyandi. High‐ T data from titanite and monazite (Catlos et al., ; Kohn et al., ; Corrie & Kohn, ; Kohn & Corrie, ; this study); intermediate temperature data from muscovite 40 Ar/ 39 Ar (Herman et al., ; Huntington & Hodges, ; Martin et al., ); low‐ T data from fission tracks; and U–Th/He (Blythe et al., ; Herman et al., ; Nadin & Martin, ; Robert et al., ). Timing of STDS movement from Murphy and Harrison (), Sachan et al.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Timing of MCT cooling varies non‐systematically along strike, with the latest and most rapid cooling at Marsyandi. High‐ T data from titanite and monazite (Catlos et al., ; Kohn et al., ; Corrie & Kohn, ; Kohn & Corrie, ; this study); intermediate temperature data from muscovite 40 Ar/ 39 Ar (Herman et al., ; Huntington & Hodges, ; Martin et al., ); low‐ T data from fission tracks; and U–Th/He (Blythe et al., ; Herman et al., ; Nadin & Martin, ; Robert et al., ). Timing of STDS movement from Murphy and Harrison (), Sachan et al.…”
Section: Discussionmentioning
confidence: 71%
“…Most intra‐GHS cut Formation I metapelites within 10 km of the MCT (e.g. Carosi et al., ; Kohn et al., ; Montomoli et al., ), for example, both the Sinuwa and Bhanuwa thrusts in the Modi Khola valley, ~50 km west of the study area (Corrie & Kohn, ; Martin, Ganguly, & DeCelles, ; Martin et al., ). In contrast, the CSZ uniquely lies ~20 km above the MCT in the orthogneiss of Formation III (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive 40 Ar/ 39 Ar dating of muscovite from Himalayan source terranes has also been used to reconstruct the thermal evolution of the Himalayan fold‐thrust belt. 40 Ar/ 39 Ar dating of muscovite from the Greater Himalayan sequence typically yields ages spanning the middle to late Miocene (Bollinger et al, ; Catlos et al, ; Coleman & Hodges, ; Copeland et al, ; Copeland et al, ; Crouzet et al, ; DeCelles et al, , ; Edwards, ; Godin et al, ; Huntington & Hodges, ; Martin et al, ; Warren et al, ; Vannay & Hodges, ;Yin et al, ). In the Kathmandu klippe in central Nepal, 40 Ar/ 39 Ar muscovite ages increase southward from circa 5 to circa 20 Ma (Herman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors consider the observed metamorphic discontinuities within the Greater Himalayan Crystallines to be second-order features not significantly affecting the extrusion of hot channel material. Martin et al (2014) date Greater and Lesser Himalaya rocks from the southern part of the Annapurna Range (central Nepal) and attribute the young Ar-Ar cooling ages to a frontal ramp and/or motion on a cross-cutting, northeast-trending fault. They infer the presence of a shear zone (the Bhanuwa fault) with a normal sense of motion.…”
mentioning
confidence: 99%